Perspectives on Improving Teaching in Canadian Universities - Wright, W. Alan; O’Neil, M. Carol (Canadian Journal of Higher Education, 1994)
As a result of increasing concerns about the quality of higher education in Canada, many universities have implemented programs and policies aimed at improving teaching. This study examines the perceptions of those individuals who are primarily responsible for teaching improvement activities at fifty-one Canadian degree-granting institutions. Respondents indicated the potential of each of thirty-six practices to improve teaching at their respective institutions. The findings reveal a widespread belief that the greatest teaching improvement potential lies in the provision of incentives to faculty in the form of employment rewards (appointment, tenure, promotion). The role of department heads, deans, and senior administrators in creating an institutional culture which encourages effective instruction is also seen as an important component of a teaching-improvement strategy. Other areas considered include activities and support structures which provide opportunities for faculty to develop their teaching abilities. Practices which seek to evaluate instruction for the purposes of making personnel decisions were seen as having the least potential to improve teaching.